Familial dementia with frontotemporal features associated with Met146Val presenilin-1 mutation - Riudavets, Miguel Angel (2013)
Most of the mutations in the presenilin-1 gene (PS-1) are associated with familial Alzheimer's disease (AD). However, certain examples can be associated with frontotemporal dementia (FTD). We performed a clinical evaluation of individuals belonging to a family with the FTD phenotype, and additional molecular studies and neuropathological assessment of the proband. The PS-1 M146V mutation was found in the 50-year-old subject (the proband) with family history of early-onset FTD. Neuropathological examination showed abundant amyloid plaques, widespread neurofibrillary pathology, Pick bodies in the hippocampus and cortex, cortical globose tangles and ubiquitin-positive nuclear inclusions in white matter oligodendrocytes. We report a kindred with clinical features of FTD, whose proband bore the PS-1 M146V mutation and showed diffuse Alzheimer's type pathology and Pick bodies on post-mortem neuropathological examination. As with other mutations within the same codon, this substitution may predispose to both diseases by affecting APP and/or tau processing.